Frequency of ventilator circuit changes to prevent ventilator‐associated pneumonia in neonates and children—A systematic review and meta‐analysis. Issue 6 (13th March 2021) - Abiramalatha, Thangaraj; Ramaswamy, Viraraghavan Vadakkencherry; Thanigainathan, Sivam; Pullattayil, Abdul Kareem; Kirubakaran, Richard
Abstract: Objective: To assess the effect of different frequencies of ventilator circuit changes in neonates and children through a systematic review and meta‐analysis. Interventions: (1) "No routine change of ventilator circuit (unless visibly soiled)" versus "routine change at any fixed interval"; (2) routine change of circuit at "less frequent" versus "more frequent" intervals. Outcomes: Primary outcomes were VAP rate (number of VAP episodes per 1000 ventilator‐days) and all‐cause mortality before discharge. Methods: MEDLINE, CENTRAL, EMBASE, and CINAHL were systematically searched from inception till November 3, 2020. Two authors assessed trial eligibility and risk of bias, and independently extracted data. Data were synthesized using fixed effects model. GRADE was used to assess certainty of evidence (CoE). Results: We identified six studies enrolling 768 participants evaluating circuit changes at two fixed intervals. Meta‐analysis of studies on circuit changes "once in less than 7 days" versus "once weekly" showed no difference in VAP rate (risk ratio: 0.83 [0.38–1.81]; one randomized controlled trial (RCT) and 0.94 [0.49–1.81]; two before‐after studies) or mortality before discharge (0.67 [0.34–1.3]; one RCT and 1.01 [0.63–1.64]; two before‐after studies). CoE was very low. Less frequent circuit changes reduced health‐care costs. No study evaluating "circuit changes only when visibly soiled" versus "circuit changes at a fixed interval" was identified. Conclusion: There is no evidence to suggest that ventilator circuits can be safely left unchanged until visibly soiled in neonates and children. Extending circuit changes interval to "once weekly" may not increase VAP rate (CoE—very low) and reduces healthcare costs.